2020
DOI: 10.1103/physrevresearch.2.033520
|View full text |Cite
|
Sign up to set email alerts
|

Apparent superballistic dynamics in one-dimensional random walks with biased detachment

Abstract: The mean-squared displacement (MSD) is an averaged quantity widely used to assess anomalous diffusion. In many cases, such as molecular motors with finite processivity, the dynamics of the system of interest produce trajectories of varying duration. Here, we explore the effects of finite processivity on different measures of the MSD. We do so by investigating a deceptively simple dynamical system: a one-dimensional random walk (with equidistant jump lengths, symmetric move probabilities, and constant step dura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…This value is on par with the speed of biological motor proteins. , Furthermore, analyses of 280 motors confirmed that most tracked particles (85%) were super diffusive with an average α = 1.37 (Figure g). A recent modeling study showed that in systems where motors progressively dissociate from the surface, selecting only the track-bound BBRs for analysis can lead to bias and an overestimate of α . However, in our system, we observed that a subset of motors tend to stall as well as dissociate over longer observation times.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…This value is on par with the speed of biological motor proteins. , Furthermore, analyses of 280 motors confirmed that most tracked particles (85%) were super diffusive with an average α = 1.37 (Figure g). A recent modeling study showed that in systems where motors progressively dissociate from the surface, selecting only the track-bound BBRs for analysis can lead to bias and an overestimate of α . However, in our system, we observed that a subset of motors tend to stall as well as dissociate over longer observation times.…”
Section: Resultsmentioning
confidence: 49%
“…A recent modeling study showed that in systems where motors progressively dissociate from the surface, selecting only the track-bound BBRs for analysis can lead to bias and an overestimate of α. 44 However, in our system, we observed that a subset of motors tend to stall as well as dissociate over longer observation times. Careful analysis of α confirmed that most S15).…”
Section: Resultsmentioning
confidence: 50%
“…For each multivalency and span combination, we simulate N = 500 trajectories for walkers that remain processive and N = 20 000 trajectories for nonprocessive walkers. The N trajectories are then analyzed by an ensemble trajectory-averaged mean squared displacement (MSD ETA ) given by Δ r j 2 is the squared displacement of the walker in the j th trajectory at time-lag τ, T j is the duration of the j th trajectory, and Δ t is the simulation timestep . The position of a multivalent walker is defined as the mean position of all bound feet and is used to compute the walker’s displacement, Δ r j .…”
Section: Model and Methodsmentioning
confidence: 99%
“…The mean squared displacement was calculated in two ways denoted by MSD TA and MSD ETA [58]. The trajectory-averaged MSD TA is computed independently for each trajectory and uses the mean of the squared displacements for each time lag τ : MSD TA,j (τ ) ≡ ∆r…”
Section: Methodsmentioning
confidence: 99%